The Relationship Between Internet Addiction and Academic Procrastination Among Eighth-Grade Students at SMPN 1 Cigudeg - Indah Habibah; Rusdi Kasman; Noneng Siti Rosidah (al-Afkar, Journal For Islamic Studies, 2026)
Academic procrastination behavior among students has become an important issue in the world of education. One of the factors that contribute to academic procrastination is the tendency of students to do other more enjoyable activities, such as spending time on the internet. Internet addiction often distracts students from their academic tasks, because they prefer to surf social media, watch videos, or play games rather than complete schoolwork. Therefore, this study aims to investigate the relationship between internet addiction and academic procrastination in grade VIII students of SMPN 1 Cigudeg. The method used in this study is a quantitative approach with a correlational model. The research sample consisted of 80 students selected using random sampling techniques. Data collection techniques were carried out through questionnaires. The results of the study showed that students experienced internet addiction in the moderate category, with a percentage reaching 85.0%. In addition, the majority of students were also in the moderate category regarding the level of academic procrastination, which reached 88.8%. The results of the correlation analysis showed a significant and positive relationship between internet addiction and academic procrastination, with a correlation coefficient value of 0.572.